Functional characterization of a novel synthetic herbicide resistance gene in a model plant - Sarwat,; Shoukat, Shehla; Zia, Muhammad Amir; Ali, Shaukat (Universiti Kebangsaan Malaysia, 2023)
As crop losses can occur owing to the abrupt growth of uncontrollable weeds in the field, research is currently being conducted in Pakistan to eradicate herbs. To carry out our proposed research domain, we have designed a novel synthetically modified EPSPS gene that has a potent role in herbicide-resistance development. The novel codon-optimized synthesized mEPSPS sequence was inserted into the pXCSG-mYFP plant expression vector. Results of colony PCR (1400 bp) confirmed the integration of genes into bacteria. For functional validation of pXCSG-mYFP-EPSPS, transient expression in tobacco (Nicotiana benthamiana) in comparison with PBSF-16 was done. Benth infiltration results showed that transient expression was successfully confirmed through ELISA and western blot analysis via anti-YFP antibody in tobacco leaves. For further validation of transient expression, the stable transformation results of the pXCSG-mYFP-EPSPS vector showed that successful transformation was done via two days of co-cultivation followed by selection and regeneration of transformed tobacco plants. The regenerated tobacco plants were then confirmed through gene-specific-based PCR. After PCR-based confirmation, western blot further validates the 26 kDa anti-YFP antibodies expression in transformed tobacco plants. Another important finding of the study was the bar and PAT gene real-time expression elucidating that the bar gene was 4.9-fold more expressive under the 35S promoter than the PAT gene under the nos promoter.